Water governance in two urban African contexts: agency and action through participatory video. (1st February 2022) - Tremblay, Crystal; Harris, Leila M.
Abstract : page_1 other This paper describes and critically examines the process and outcomes of a community-based participatory video (PV) research project on issues related to water governance with residents of underserved and informal settlements in Khayelitsha, South Africa and Accra, Ghana. Co-produced videos were used to facilitate communication and to open a dialogue between the participating communities and their respective local governments, with the aims of improving awareness of the issues, enhancing agency and enabling participation in the political and social debates about water governance. Analysing the approach, our research draws on two key principles of participatory governance – recognition and response – to evaluate the application of PV as a potential engagement tool for participatory water governance. We critically discuss the reality and tensions of PV in shifting deep-rooted inequities of power in decision making through two case studies, both of which involved residents and representatives from local governments in the research process.